The Effectiveness of Hybrid Learning In The MPI Postgraduate Program: A CIPP Model Evaluation At UIN Siber Syekh Nurjati Cirebon - Nadliroh, Nadliroh; Azani, Fajriyan Megawati; Cahyani, Dewi; Ali, Moh (IAIN Syekh Nurjati Cirebon, 2025)
This study aims to determine how effective the hybrid learning model is in the Islamic Education Management (MPI) Postgraduate program at UIN Siber Syekh Nurjati Cirebon. The CIPP (Context, Input, Process, and Product) evaluation method is used in this study. This study uses a quantitative approach by conducting a survey of students, lecturers, and relevant stakeholders. This study uses a questionnaire that has been empirically validated. The results of the study indicate that the hybrid learning program has met the needs and directions of digital higher education policies in various contexts. In the field of input, the availability of human resources, technological infrastructure, and readiness of learning devices are considered quite good. In the field of process, the implementation of learning is effective, although several technical obstacles and variations in learning interactions are found. In the field of product, learning outcomes show a significant increase, marked by an increase in student competence. The evaluation results show that hybrid learning in the MPI Postgraduate program at UIN Siber Syekh Nurjati Cirebon is quite effective. However, technical improvements and improvements in learning interactions are still needed. This study helps develop a digital learning evaluation model in a higher education environment based on hybrid learning.